2022
DOI: 10.3390/jof8080823
|View full text |Cite
|
Sign up to set email alerts
|

How and Where Periglandula Fungus Interacts with Different Parts of Ipomoea asarifolia

Abstract: Periglandula is a fungal genus that is associated with plants in the family Convolvulaceae. They produce medicinally important constituents called ergot alkaloids, which are stored in their host plants. Previously, the fungi were reported to mainly interact with young leaves and seeds of Convolvulaceae species. However, knowledge about how ergot alkaloid-producing fungi interact with their host plants is still lacking. Therefore, we investigated the interaction of Periglandula fungus with different plant parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…As the total RNA template was a mixture of plant RNA and fungal RNA at varying ratios, these differences are likely due in part to differences in fungal biomass found on different plant parts. The three parts of I. asarifolia found to have the highest dmaW expression levels were young seeds, young leaves, and ower buds, which corresponds with our previous observation of high densities of fungal hyphae on these same plant parts [24]. When comparing the expression of the three reference genes to each other, the fold differences across plant organs were similar, which also con rms variation in fungal biomass across different plant parts, with the highest biomass in young seeds and young leaves (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As the total RNA template was a mixture of plant RNA and fungal RNA at varying ratios, these differences are likely due in part to differences in fungal biomass found on different plant parts. The three parts of I. asarifolia found to have the highest dmaW expression levels were young seeds, young leaves, and ower buds, which corresponds with our previous observation of high densities of fungal hyphae on these same plant parts [24]. When comparing the expression of the three reference genes to each other, the fold differences across plant organs were similar, which also con rms variation in fungal biomass across different plant parts, with the highest biomass in young seeds and young leaves (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Periglandula fungi are primarily associated with the leaves and seeds of their host plants [21,22], and ergot alkaloids have been detected in both the leaves and seeds of the plants [20,23]. Our recent study examined numerous parts of Ipomoea asarifolia and discovered Periglandula ipomoeae on six out of eight plant parts: young folded leaves, mature leaves, ower buds, mature owers, young seeds, and mature seeds [24]. However, it is still uncertain which parts of I. asarifolia (both fungus-associated and non-associated) contain ergot alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the ergot alkaloids may contribute to chemical defense against herbivores as well as promote plant growth [ 60 , 61 , 62 , 63 , 64 ]. As this mutualism is clade-specific and found in several species that are closely related to R. ornata [ 60 , 63 , 118 ], it offers further research opportunities to determine if the foliar glands of R. ornata also influence plant–microbe interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In most symbiotic species, both the Periglandula and Chaeotothyriales symbionts are found tightly associated with the glandular trichomes on the adaxial leaf surfaces of taxa containing EAs, IDTs, and SWN (Fig. 1; Steiner et al ., 2015; Noor et al ., 2021; Neyaz et al ., 2022; Olaranont et al ., 2022). Glandular trichomes in I. pes‐caprae and I. asarifolia , which are both EA+ and IDT+, have been found to secrete polysaccharides, terpenes, and fatty acids (Martins et al ., 2012; Steiner et al ., 2015; Kuster et al ., 2016), which might act as an energy source for the endosymbiotic fungi.…”
Section: Life‐history Traits Correlation With Heritable Fungal Endosy...mentioning
confidence: 99%
“…Closely related legumes in the Astragalus, Oxytropis, and Swainsona genera (locoweeds) are symbiotic with related, SWN-producing Alternaria endosymbionts (Cook et al, 2014). In diverse morning glory species (defined as members of the large tribe Ipomoeeae with spiny pollen, family Convolvulaceae), distinct fungal endosymbionts producing SWN and EA are detectable in many host species through hyphal growth on adaxial leaf surfaces associated with oil-secreting glandular trichomes as well as between tissue types and cell layers (Neyaz et al, 2022;Olaranont et al, 2022;Fig. 1).…”
Section: Hereditary Fungimentioning
confidence: 99%